La calidad en el servicio y su relación con la satisfacción del consumidor en restaurantes categorizados de la ciudad de Iquitos - Perú 2021 - Del Águila Rios, Ceci Valeria (2022)
The research work called “Quality in service and its relationship with consumer satisfaction in categorized restaurants at the city of Iquitos - Peru 2021”, aims to determine the relationship between quality in service and consumer satisfaction at the categorized restaurants in the first quarter, of 2021; In order to meet the objective, a sample of 227 observation units was considered and they were of a probabilistic type. The instrument used was the SERVQUAL model questionnaire with Likert measurement to rate the discernment of the interviewees and thus determine the relationship between study variables. Quantitative approach research, descriptive type - correlational, non- experimental design, hypothetical method - deductive, teach abstracts and commentaries that support the theoretical foundation of the research and results that show tables and figures that support a better analysis. The results show the extension of reliability has a higher good weighting, consumers perceive satisfaction, in the customer's opinion the interaction component provides satisfaction. It concludes "There is a significant high statistical relationship between quality service and consumer satisfaction in categorized restaurants at the city of Iquitos first quarter 2021", according to Tau - Kendal b = 0,620, p-value = ? = 0,000.